Terahertz spectroscopy study of oridonin and ponicidin in the anticancer Chinese herbal medicine Rabdosia rubescens - Gao, Yang; Peng, Zhuang; Yang, Huiyu; Zhang, Xinrui; Zhao, Yuhan; Hou, Zeyu; Su, Bo; Li, Kai; Zhang, Cunlin (Frontiers in Plant Science, 2024)
Rabdosia rubescens, a Chinese herbal medicine with anticancer properties, contains two active ingredients: oridonin and ponicidin. Both compounds exhibit antitumor effects by inducing tumor cell apoptosis and autophagy and inhibiting tumor cell proliferation. To further explore the differences in molecular structure and pharmacological properties between the two substances, this study employs Terahertz Time-Domain Spectroscopy (THz-TDS) to investigate the spectral characteristics of oridonin and ponicidin in the frequency range of 0.1 to 2.3 THz. The results reveal similarities in the spectra of the two compounds, with similar absorption peaks at 1.76 and 2.14 THz. Additionally, oridonin exhibits an absorption peak at 1.55 THz, while ponicidin displays three distinct absorption peaks at 1.85, 1.96, and 2.22 THz. The crystal structures of the two substances are simulated using Materials Studio software and Density Functional Theory (DFT), yielding their spectra and molecular vibration modes, which elucidate the mechanism underlying the peak generation. The consistency between experimental and simulation results confirms the reliability of the experimental findings. Thus, THz spectroscopy can effectively distinguish between these two substances. Furthermore, microfluidic chip technology is employed to measure the spectral characteristics of the two substances in solution.The results indicate that the absorption peaks of oridonin and ponicidin in solid and solution states are generally consistent, although some absorption peaks undergo frequency shifts. Finally, a THz detection is performed on Rabdosia rubescens capsules purchased from the market, revealing the presence of absorption peaks for both substances in their absorption spectra. This provides a new approach for detecting active ingredients in Chinese herbal medicines.